(untitled) (Research, Society and Development, 2022)
Chemistry is an experimental science, therefore, for the teaching and learning process to be more relevant to students, it is important to carry out experimental activities. This study aimed to analyze the context of the Teachers of the Chemistry curricular component, assigned to Public High Schools, regarding the use of the laboratory and the execution of experimental activities. This research consisted in the application of a questionnaire to 32 teachers who teach the Chemistry component. It was possible to observe that most teachers, even facing challenges, such as lack of structure and investment, carry out experimental activities to demonstrate the topics covered in the classroom in a practical way for students. It is concluded that it is important that experimental activities are present in the teaching of chemistry, enabling teachers and students to learn the theories of science, and also to build school knowledge from questioning, discussion of arguments and validation of these arguments.